Reliability and validity of transfer assessment instrument version 3.0 in individuals with acute spinal cord injury in early rehabilitation phase - Preeti Baghel; Shefali Walia; Majumi M Noohu (World Scientific Publishing, 2018)
Background: Transfers are very important in functional activities of subjects with spinal cord injury (SCI). The transfer assessment instrument (TAI) was the first tool to standardize the assessment of transfer technique. Objective: The purpose of this study was to establish the reliability and validity of TAI 3.0 in people with SCI in early rehabilitation phase. Methods: Thirty subjects with acute traumatic SCI were recruited from a tertiary care center for SCI management. Four raters assessed the quality of transfer using TAI 3.0 and a fifth rater used global assessment of transfer scale (VAS). TAI 3.0's intraclass correlation coefficient (ICC) for intrarater and interrater reliability, standard error of measurement (SEM), minimal detectable change (MDC), limits of agreement and concurrent validity was determined. Results: The intrarater ICC was 0.93 to 0.98 and interrater ICC was 0.99, indicating high levels of reliability. The SEMs among the raters for TAI 3.0 total was from 0.23 to 0.28. The MDC among the raters TAI 3.0 total was from 0.54 to 0.86. Correlation for different raters between the TAI 3.0 and VAS ranged between 0.88 and 0.90. Conclusion: TAI 3.0 is a reliable and valid tool to assess the transfer skill in individuals with SCI in early rehabilitation phase.